EFFECT OF TRANSCRANIAL DIRECT CURRENT STIMULATION ASSOCIATED WITH PROPRIOCEPTIVE EXERCISES IN CHILDREN AND PRE-ADOLESCENTS WITH ACQUIRED AND CONGENITAL VISUAL IMPAIRMENT: RANDOMIZED CLINICAL TRIAL (CIPEEX, 2022)
In the absence of information from the visual system, balance is guided by only two of the three afferent systems. If there is no early stimulation of these systems, blind children tend to become passive, which can have a negative impact on muscle tone, coordination, and balance. The objective of the present study was to analyze whether transcranial direct current stimulation (tDCS) is capable of enhancing the effects of static and dynamic proprioceptive exercises on gait and balance control in children and pre-adolescents with acquired or congenital visual impairment. The study will be conducted after approval by the Research Ethics Committee of the Evangelical University of Anápolis, Anápolis, GO, Brazil (certificate number: 4610052.6.0000.5076). The study will be divided into three phases. Phase 1 will be a cross-sectional study for the characterization of gait, postural control, and balance (static and dynamic) in the sample. Phase 2 will be a pilot study that will serve to determine the sample size for Phase 3. Both phases 2 and 3 will employ the same methods and will constitute a randomized, controlled, double-blind clinical trial. The participants will be randomly divided into four groups: G1) Active TENS + static proprioceptive exercises; G2) simulated TENS + static proprioceptive exercises; G3) active TENS + dynamic proprioceptive exercises; G4-sham TENS + dynamic proprioceptive exercises. The results will be based on evaluations conducted at three time points (pre-intervention, post-intervention [after ten treatment sessions], and one-month follow-up) and will involve three-dimensional gait analysis, as well as assessments of functional mobility and balance (static and dynamic).
Keywords: Children; Blindness; Transcranial stimulation; Gait